SEASONAL VARIATIONS IN ZOOPLANKTON COMMUNITY OF AN AQUATIC ECOSYSTEM AT SUSURLUK BASIN (BALIKESIR-TURKEY) - Bulut, Hilal; Saler, Serap (Parlar Scientific Publications (P S P), 2018)
In this study, zooplankton community, assessment with index analysis and cluster analysis were studied seasonally, between winter 2013 - autumn 2014. Zooplankton samples were collected from three different stations with plankton net, both horizontally and vertically. In the dam lake 26 zooplankton species were identified. Zooplankton samples were consisted of 17 Rotifera, six Cladocera, and three Copepoda, respectively. Rotifera was the dominant group of zooplankton with regard to species numbers and densities.
Keywords: Rotifera; Cladocera; Copepoda; index analysis